EFFECT OF COATING THICKNESS ON ADHESIVE WEAR RESISTANCE OF ELECTRODES FOR WELDING OVERLAY - Oñoz Gutiérrez, Pablo; Rodríguez Pérez, Manuel; Perdomo González, Lorenzo; González Pérez, Ulises José; Rosquete Rivas, Ruel; González Molina, Nilo (Centro Azúcar Journal, 2025)
Introduction: An effective way to increase the durability of parts is to apply a hard welding overlay. The production of these electrodes in Cuba is vital, as the country has the necessary infrastructure and raw materials. Objective: To determine the operational and metallurgical properties of the ECromita 1 and ECromita 2 electrodes, as well as the influence of coating thickness on their resistance to adhesive wear, in comparison with a commercial electrode (UTP 620). Materials and Methods: The operational properties were evaluated using expert criteria and quantitative methods. Weld deposits were characterized by optical spectrometry, metallography, hardness measurement, and adhesive wear tests (pin-on-disc). Results and Discussion: The operational properties were suitable for industrial use. The ECromita 2 deposit in the as-welded condition showed greater resistance to adhesive wear than UTP 620. ECromita 1 was less resistant in this state, with potential for improvement through heat treatments. Conclusions: The ECromita 2 electrode has operational properties and resistance to adhesive wear that make it a viable solution for industrial application, specifically in the restoration of parts damaged by this wear mechanism.